A material removal rate model-based chemical action of ultra-thin SUS304 substrate in chemical mechanical polishing. Issue 1 (July 2016) - Wei, Xin; Yang, Xiangdong; Xie, Xiaozhu; Hu, Wei
Abstract In this study, a mathematical model of material removal rate (MRR) is developed to investigate the chemical action during chemical mechanical polishing (CMP) of ultra-thin SUS304 substrate (thickness <0.1 mm) based on the theoretical analyses and the experiments. It is found that as the mass concentration of oxidants increases, the material removal rate of SUS304 substrate increases at first, then decreases. Additionally, the relationship between the MRR and the flow rate of the polishing slurry is observed. The MRR is proportional to the flow rate of acidic self-made polishing slurry. Furthermore, a better ultra-thin SUS304 substrate surface quality may be obtained after CMP when the mass concentration of H2 O2 is 7.5 %. The present study also investigates the chemical and mechanical synergetic action mechanisms of the CMP process of SUS304 substrate.